Obesity & Physical Activity - Schulz SVW; Jacobsen E; Prokopchuk D; Otto S; Steinacker JM; Schulz AS (Deutsche Zeitschrift für Sportmedizin)
Introduction: A stem cell transplantation (SZT) leads to considerable physical and mental strain. It is shown that physical activity helps to cope with medical therapies. In this case report, the possibilities of modern training will be described as an example.Methods: A patient with acute myeloid leukaemia (AML) has been supervised sports-medically 2x/week over one year after allogeneic SZT. In hospital she trained with very short intervals (5-10x20sec) and 2-4 weight exercises (5-10 repetitions; 2 series) according to the Borg scale (<14). Ambulant the bicycle and treadmill ergometer was used with 2-5x1-10min intensive intervals at 90% HFpeakalternating with at least equally long intervals at 70% HFpeak. Strength training was combined (4-6 exercises; 10-15 repetitions; 2-3 series; Borg <15). At the end of sports therapy 10 km of run could be finished. A spiroergometry examined the results of ambulant training.Results: The maximum oxygen uptake increased by 14.60ml/min/kg (57.71%), the individual anaerobic threshold (IAS) 54,9 Watt (96,7%), the training weight 136,8 Watt (118.8%), haemoglobin 4.00g/dl (38.10%), thrombocytes 22.00 Giga/l (12.57%) and leucocytes 2.00 Giga/l (66.67%). During the 10km run there was a decrease of NK-, T- and cytotoxic T-cells.Discussion: This case indicates exemplarily the great possibilities of the sports-medical training, which begins in hospital and is continued in an intensified ambulant aftercare.KEY WORDS: Allogeneic Stem Cell Transplantation, Acute Myeloid Leukaemia, Interval Training, 10km Run